PERSEPSI PRIA MILENIAL PADA PRODUCT LABELING SKINCARE - Kastella, Yulia Cahyawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2023)
The consumption patterns of society have shown an annual increase, one example being found in purchasing and usage of skincare products. Skincare products have seen a rise in popularity not only among women but also among millennial men, particularly in the Jabodetabek region. This phenomenon can be attributed to the offerings from manufacturers, both international and local brands, which have experienced significant growth. One of the factors influencing consumer perception is the information presented through media channels regarding the functions and composition of products, the country of origin label (local or imported), product certification labels such as BPOM, Halal, and environmentally friendly labels (animal cruelty-free, vegan, organic, natural, non-toxic, eco-friendly, and fair trade). This research employs a qualitative descriptive method, involving interviews with 12 millennial men residing in the Jabodetabek area. The findings reveal that millennial men do not give too much consideration to product labeling on skincare items. The majority of respondents tend to choose products based on their specific needs and often to buy for bundled product packages.